Jana Mynářová, Pavel Onderka and Peter Pavúk (eds). There and Back Again – The Crossroads II. Proceedings of an International Conference Held in Prague, September 15-18, 2014. - Dickinson, Oliver (Journal of Greek Archaeology, 2017)
This publication in a handsome-looking hardback volume of the papers given at a recent conference in Prague is large (24 papers) and diffuse, but has Egypt and its ‘rich and complex relations with the Levant, the Aegean and the Sudan’ in the 2nd and 1st millennia, particularly the later Bronze Age, as its central theme. The majority of the papers concentrate on texts, which can provide valuable evidence even when material objects or artistic representations are the subject of the paper. They offer a salutary reminder of the sheer range and quality of documentation available from fully literate civilisations like those of Egypt and the wider Near East, and make a striking contrast with Aegean prehistory, which depends, for lack of written sources, on hypotheses that are always liable to change as a result of new archaeological discoveries and/or to be reinterpreted in the light of new theories and approaches.